Обрaз телa и его последствия - Alpysbayeva, A. S.; Mun, M. V. (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2018)
Adolescents’ body image is a crucial factor of their health and wellbeing. The term body image has strong roots and dimensions. Until nowadays, there were many researches were done about importance of body image in certain ages, the causal factors of body image and about its influence on general human psychological and physiological well-being. Current article aims to describe body image from develop¬mental perspective, how it is formed and influenced during childhood, adolescence and adulthood pe¬riods of human life and what kind of changes body dissatisfaction can cause in their personal and social life. Our main focus will be about influence of negative personal body image on social anxiety among teenage girls. We expect that body dissatisfaction is one of the main causes of social anxiety which pre¬vents teenagers being active, social, integrated with other people. On the other hand, social anxiety has negative influence on self-esteem, interpersonal relationship of teenager which have negative influences on their overall successful development. In further researches we believe that awareness of people about importance of body image perception will be helpful to create different kind of trainings will be influen¬tial in individuals’ overall self, success in personal and social life. Key words: body image, social anxiety, teenagers.